Sustainable logistics network design for multi-products delivery operations in B2B e-commerce platform - Prajapati D.; Zhou F.; Zhang M.; Chelladurai H.; Pratap S. (My University, 2025)
This paper investigates an integrated supplier selection, vehicle routing, and transportation problem with sustainability factors (like economical and environmental) for (B2B) e-commerce logistics network design, which supplies the multi-product order from the supplier node to the retailer node. In this, we have formulated a mixed-integer nonlinear programming (MINLP) model to minimize the total transportation cost, penalty cost due to late pickup and late delivery, and fuel consumption cost with the best possible supplier selection and find the route for delivery of an order batch. Two solution approaches, i.e., exact optimization using LINGO solver and meta-heuristics, i.e. Invasive Weed Optimization (IWO) and Simulated Annealing (SA) used to solve the proposed model. We have tested the model on 10 scenario (i.e. Small to large size problems) and computation experiments reveal that Simulated Annealing performs better than Invasive Weed Optimization. The study is expected to benefit E-commerce company and helps the manager in perspective of logistic service and supplier selection. © 2021, Indian Academy of Sciences.